Machine Learning and Artificial Intelligence for the Development of Social Responsibility and Risk Management Techniques - Walker Diaz Panduro, Jorge Lázaro Franco Medina, Jesus Enrique Reyes Acevedo, Rosa Maria Velarde Legoas, Roberto Alejandro Pacheco Robles, Yuli Novak Ormeño Torres (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In an era marked by unprecedented technological advancements, Machine Learning (ML) and Artificial Intelligence (AI) are emerging as powerful tools for promoting social responsibility and enhancing risk management practices. This paper explores the transformative potential of ML and AI in addressing societal challenges and fortifying risk mitigation strategies. The intersection of ML and AI with social responsibility endeavors opens avenues for proactive engagement and impactful interventions. Through sentiment analysis and social media monitoring, AI algorithms enable organizations to gauge public perceptions, identify emerging issues, and tailor their initiatives to address societal needs effectively. Moreover, ML-powered predictive analytics facilitate data-driven decision-making, enabling businesses to anticipate and respond to social and environmental risks proactively. Furthermore, AI and ML technologies offer novel approaches to risk management across various domains. In the financial sector, predictive modeling and algorithmic trading algorithms enhance risk assessment and portfolio optimization, bolstering resilience against market fluctuations. In healthcare, ML algorithms analyze patient data to identify potential health risks and optimize treatment strategies, thereby improving patient outcomes and reducing healthcare costs. However, the adoption of ML and AI for social responsibility and risk management also poses ethical and regulatory challenges.